Tradução e adaptação transcultural do instrumento de avaliação Prenatal Self-Evaluation Questionnaire - Silva, Janiny Lima e (2010)
Introduction: The human gestation period is 40 weeks. This is the essential time for maternal psychosocial adaptation, in which there is the intense transformation of a life without offspring into a life with one or more children. The Pregnancy Self-Evaluation Questionnaire (PSEQ) has 79 items, subdivided into seven subcategories: acceptance of pregnancy, identification with the maternal role, well-being of mother and baby, preparing for labor, control in labor, relationship with the mother and the relationship with the partner. Objective: To translate and cross-culturally adapt the instrument PSEQ to be used with Brazilian women. Methods: It is a cross-sectional observational study. We followed some methodological steps to achieve the cross-cultural adaptation of this measuring instrument. They are: translation, synthesis, back translation, analysis of the committee of specialists and pre-test. Another questionnaire was applied to characterize the socio-demographic and clinical status of the pregnant women (n = 36). The descriptive statistics was gotten through the average, standard deviation (SD), absolute and relative frequency. The statistical test used for the analysis of the internal consistency was Cronbach's alpha coefficient, using SPSS version 17.0. Results: The volunteers had low socioeconomic status, average age of 25.1 years (± 5.52), and average gestational age of 25.9 weeks (± 8.11). 58.3% of these volunteers had not planned their current pregnancy. The pretest showed that 75% of pregnant women found the questionnaire easy to understand. There was an average of 76.9 (± 3.23) answered items among the participants. Regarding the instrument PSEQ, the identification with the maternal role was the subcategory which showed the highest average 24.8 (± 5.6), while the relationship with the mother had the lowest average 15.4 (± 7.7). The internal consistency ranged from 0.52-0.89. Conclusion: The translation and cross-cultural adaptation of the PSEQ to Portuguese language were carried out with methodological rigor and can be considered an instrument with good internal consistency